2020
DOI: 10.1155/2020/5014916
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Leg Elevation to Prevent Spinal Anesthesia-Induced Hypotension during Cesarean Delivery in the Resource-Limited Area: Open Randomized Controlled Trial

Abstract: Background. Postspinal hypotension is the most common complication after spinal anesthesia for cesarean section (CS). Hypotension mainly occurs due to the reductions of vascular tone leading to decreased systemic vascular resistance and decreased venous return. The aim of this study was to assess the effectiveness of leg elevation (LE) as a method of prevention of postspinal hypotension in patients who undergo cesarean section under spinal anesthesia. Methods. This is a single-center parallel-randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…the control group (33.3% vs. 62.5%, p=0.02) (9). Also, in line with the results of the study conducted by Hasanin et al, the hypotension incidence in the group administrated with a 40-degree LR in the horizontal plane was observed to be much lower than in the control group (34.7% vs. 58.7%, p=0.005) (7).…”
Section: Discussionsupporting
confidence: 84%
“…the control group (33.3% vs. 62.5%, p=0.02) (9). Also, in line with the results of the study conducted by Hasanin et al, the hypotension incidence in the group administrated with a 40-degree LR in the horizontal plane was observed to be much lower than in the control group (34.7% vs. 58.7%, p=0.005) (7).…”
Section: Discussionsupporting
confidence: 84%
“…The proportion of patients developing hypotension in this study was 56.7%, which is consistent with previous research. (5,13,14) Hypotension is a well-known complication of spinal anesthesia, and its occurrence can have signi cant implications for both the mother and the fetus. (3)…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies indicate that hyperbaric bupivacaine leads to reduced post-spinal hypotension and a quicker achievement of maximum sensory and motor block compared to isobaric bupivacaine. 16–18 Other studies found minimal post-spinal hypotension and a faster onset of block in the isobaric bupivacaine group than in the hyperbaric bupivacaine group. 18 , 19 This controversy calls for a well-designed study to compare the two groups in terms of their effects on hemodynamic profiles and block characteristics.…”
Section: Introductionmentioning
confidence: 90%